2009
DOI: 10.1111/j.1466-8238.2009.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

The variation of apparent crown size and canopy heterogeneity across lowland Amazonian forests

Abstract: International audienceAim: The size structure of a forest canopy is an important descriptor of the forest environment that may yield information on forest biomass and ecology. However, its variability at regional scales is poorly described or understood because of the still prohibitive cost of very high-resolution imagery as well as the lack of an appropriate methodology. We here employ a novel approach to describe and map the canopy structure of tropical forests. Location Amazonia. Methods: We apply Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 51 publications
1
112
1
1
Order By: Relevance
“…[39] demonstrated that crown allometries are less affected than stem allometries to site factors, making the former more suitable for predicting forest parameters. In terms of texture, the selection of the third PCA axis (FC3 or FD3) is somehow contradictory with previous studies where it was noted that most of the textural information is synthetized along the two first PCA axes [54]. However, additional research is needed to fully understand the link between FOTO metrics and forest parameters in a range of forest conditions.…”
Section: Model Performancecontrasting
confidence: 44%
“…[39] demonstrated that crown allometries are less affected than stem allometries to site factors, making the former more suitable for predicting forest parameters. In terms of texture, the selection of the third PCA axis (FC3 or FD3) is somehow contradictory with previous studies where it was noted that most of the textural information is synthetized along the two first PCA axes [54]. However, additional research is needed to fully understand the link between FOTO metrics and forest parameters in a range of forest conditions.…”
Section: Model Performancecontrasting
confidence: 44%
“…A macrostructure of crown size has been detected by [55] in Amazonia terra firme forests. Despite the high local variability, apparent crown size tends to be larger than 16 m in a broad east-west band, from 5-10° of the equator, and larger than 15 m in the contiguous region in north-eastern Amazonia.…”
Section: Crown Size and Leaf Size Patternsmentioning
confidence: 99%
“…Developing methods for the extraction of texture is a key priority to retrieve information on canopy conditions from forest structure [32]. However, texture derived from 3D InSAR datasets has not yet been explored to obtain information related to canopy heterogeneity and in particular for the analysis of differences in structure between landscapes, which are characterized by a gradient of heterogeneity derived from anthropogenic disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Also forest disturbance has been addressed using these techniques (e.g., selective logging: [52,53]). Canopy grain analysis from FOTO applied to LiDAR derived Canopy Height Model (CHM) and Digital Surface Model (DSM) was also used to generate metrics related to structure and to ultimately improve above-ground biomass prediction [32,54]. The extraction of single crowns from LiDAR has also been explored [55].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation